2015
DOI: 10.1111/cxo.12248
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision syndrome in presbyopia and beginning presbyopia: effects of spectacle lens type

Abstract: Purpose: This office field study investigated the effects of different types of spectacle lenses habitually worn by computer users with presbyopia and in the beginning stages of presbyopia. Computer vision syndrome was assessed through reported complaints and ergonomic conditions. Methods: A questionnaire regarding the type of habitually worn near-vision lenses at the workplace, visual conditions and the levels of different types of complaints was administered to 175 participants aged 35 years and older (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
(49 reference statements)
3
29
0
Order By: Relevance
“…Participants may have used a 2.3 degrees higher head inclination with general purpose PALs (15.4 ± 5.2 degrees, eye‐ear line relative to horizontal) compared to computer vision PALs (13.1 ± 5.1 degrees) to compensate for this difference (at least in part). Significantly higher head inclinations with general purpose PALs were also found in other studies in relation to single near vision lenses that also do not restrict head position: the effect was 4.6 degrees (16.3 ± 6.9 versus 11.7 ± 5.1 degrees) (Weidling and Jaschinski, unpublished data) and 6.8 degrees (17.4 ± 9.2 versus 10.6 ± 9.4 degrees), respectively. Ergonomic studies report a favourable head inclination in the range of eight to 15 degrees (eye‐ear line relative to the horizontal) to avoid musculoskeletal strain.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Participants may have used a 2.3 degrees higher head inclination with general purpose PALs (15.4 ± 5.2 degrees, eye‐ear line relative to horizontal) compared to computer vision PALs (13.1 ± 5.1 degrees) to compensate for this difference (at least in part). Significantly higher head inclinations with general purpose PALs were also found in other studies in relation to single near vision lenses that also do not restrict head position: the effect was 4.6 degrees (16.3 ± 6.9 versus 11.7 ± 5.1 degrees) (Weidling and Jaschinski, unpublished data) and 6.8 degrees (17.4 ± 9.2 versus 10.6 ± 9.4 degrees), respectively. Ergonomic studies report a favourable head inclination in the range of eight to 15 degrees (eye‐ear line relative to the horizontal) to avoid musculoskeletal strain.…”
Section: Discussionsupporting
confidence: 75%
“…The present sample comprised 23 users of general purpose PALs who had reported a relatively higher level of ocular and musculoskeletal strain in a preceding study one year earlier . At the start of the present study, they showed an average level of complaints, which can be explained by the typical effect of regression to the mean .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this way, the participants became acquainted with the procedure; even if single untypical postures may have been measured, these data will little affect the average of a series per day. The present method has been proven as useful in our previous studies because we found reliable individual changes in workplace postures after an office intervention (Meinert, König, and Jaschinski 2013) and a significantly higher head inclination by 2 -78 in users of generalpurpose progressive lenses (Jaschinski et al 2015a(Jaschinski et al , 2015b. The present results on head inclination in Figure 8 based on intra-individual comparisons further confirm this procedure.…”
Section: Dependent Measuressupporting
confidence: 81%
“…Thus, for clear near vision, spectacle lenses are required. Spectacles with general-purpose progressive lenses are most frequently used (Jaschinski et al 2015a) due to their advantage of a gradual vertical change in near vision addition across the lens. This allows for clear vision at any viewing distance from far (e.g.…”
Section: Introductionmentioning
confidence: 99%